Dentistry and Ayurveda - IV: Classification and management of common oral diseases - Amruthesh Sunita (Wolters Kluwer Medknow Publications, 2008)
This article, the fourth in the series titled ′Dentistry and Ayurveda,′ describes in brief the panchakarma therapy, which is a distinctive feature of the Ayurvedic method of detoxifying the body. The various therapies and medicines used in Ayurveda have been elaborated. Further, an attempt has been made to correlate dental diseases in Ayurveda with the modern-day classification, clinical features, and management.